A transportable temperature and heatwave control device (TENTACLE) for laboratory and field simulations of different climate change scenarios in aquatic micro- and mesocosms. (April 2022) - Hermann, Markus; Jansen, Richard; van de Glind, Johan; Peeters, Edwin T.H.M.; Van den Brink, Paul J.
Graphical abstract: Abstract: Future global climate change with higher mean temperatures and increased intensity and frequency of heatwaves as extreme weather events will affect aquatic ecosystems with, yet, unpredictable severity and consequences. Although models suggest increased risk of species extinction up to the year 2050 for series of different climate change scenarios, environmental complexity may result in unconsidered effects of future temperature alterations on ecosystems. Apart from these environmental changes, additional anthropogenic stressors, e.g. chemical release, may cause unprecedented interaction effects on ecosystems. Ongoing efforts to better understand such temperature-chemical interaction effects comprise almost exclusively experimental designs using constant temperature regimes instead of environmentally realistic daily temperature variations. In this paper we describe an Arduino-based temperature and heatwave control device (TENTACLE) that is transportable, inexpensive, multifunctional, and easily reproducible. TENTACLE offers water temperature monitoring and manipulation of up to 3 different climate change-related scenarios: i) natural (ambient) sinusoidal fluctuations (laboratory applications), ii) elevated fluctuations, and iii) heatwaves as extreme events. The use of replaceable heating elements and low-cost materials suitable for field studies creates a high flexibility for researchers who may conduct in- or out-door, small- or large-scale, fresh- or salt-water experiments at different geographical locations.